Tinjauan Pustaka: Prenatal Yoga Untuk Kecemasan Dalam Kehamilan - Budi Rahayu; Ristiana Eka A. (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Physiological and psychological changes during pregnancy affect anxiety in pregnant women. Such anxiety will have a major impact on childbirth preparation and also face the birth of the baby. This anxiety if not minimized during pregnancy has an impact on the psychological of pregnant women and nifas. Therefore the purpose of this literature study is to find out the benefits of prenatal yoga to overcome anxiety in pregnancy. The Google Scholar database is used to search for research articles. Literature searches using the keywords pregnancy, prenatal yoga, anxiety with rriteria inclusion articles used are articles from 2013-2021, primary articles, fulltext and research subjects of pregnant women. Based on the above search obtained 306 articles based on keywords and six articles will be analyzed with a descriptive narrative approach in this paper. Of the 306 research articles, seven articles were reviewed that met all the inclusion criteria and objectives of this literature study. Seven articles obtained were then conducted critical appraisal which was then analyzed using simplified thematic analysis. The sample criteria of pregnant women in the article are primigravida pregnant women, TM II and TM III gestational age, yoga at least 4x in pregnancy. Based on the results of this article review, by doing prenatal yoga regularly able to reduce the condition of anxiety in pregnant women.